Vriesea serraourensis (Bromeliaceae: Tillandsioideae), a new species from Chapada Diamantina, Bahia, Brazil - Souza, Everton Hilo De; Fernandez, Eduardo P.; Ferreira, Glaucia C.; Aona, Lidyanne Y. S.; Souza, Fernanda V. D.; Leme, Elton M. C. (Phytotaxa, 2025)
We describe, discuss, and illustrate Vriesea serraourensis, a new species from the Chapada Diamantina in the municipality of Barra da Estiva and Ituaçu, Bahia, Brazil, here considered a critically endangered species. The new species is morphologically related to V. bahiana but clearly differs from it by its larger size, longer and fewer leaves, inflorescence branches forming an internal angle of 30o–45o with the main axis, sepals yellow and ovate, petals narrowly obovate, whitish-yellow towards the base and yellow at the apex, and basal petal appendages with acuminate or irregularly bidentate apex. Additionally, we provide the phenology of the new species.